Staff attributions about the causes of challenging behaviours - Grey, Ian M. (2002)
Staff attributions for challenging behaviour are purported to relate to staff responses to such behaviour. To elucidate this relationship, much recent work has relied on eliciting staff attributions to written descriptions of a client engaging in challenging behaviour. However, current attribution theory suggests that eliciting attributions in relation to written descriptions is likely to be qualitatively different from attributions to known clients with challenging behaviour. Thirty-four staff completed the Challenging Behaviour Attribution Scale (CHABA) with respect to a client with whom they worked before, during and after completing a longitudinal course in assessment and intervention for challenging behaviour. Significantly more staff attributed challenging behaviour to negative reinforcement and self-stimulation after training. There was a significant reduction in the number of staff attributing challenging behaviour to positive reinforcement after training. However, a number of deficiencies in the CHABA were identified which may render interpretations inconclusive.